Potential recovery of phosphorus during the fluidized bed incineration of sewage sludge. (1st January 2017) - Li, Rundong; Teng, Wenchao; Li, Yanlong; Wang, Weiyun; Cui, Ruoqi; Yang, Tianhua
Abstract: Phosphorus is a limited non-renewable resource that is indispensable as an essential nutrient for the growth of organisms in most ecosystems. To demonstrate the reuse of phosphorus resources from sewage sludge ash (SSA), experiments were conducted in a pilot circulating fluidized bed kiln. The experimental results demonstrated that high temperature and calcium oxide (CaO) were beneficial for the transformation of non-apatite inorganic phosphorus (NAIP) to apatite phosphorus (AP). Thermogravimetric differential scanning calorimetry analysis was combined with X-ray diffraction measurements to simulate the process of sewage sludge incineration of the crystal phase transition between aluminium phosphate (AlPO4 ) and CaO, forming stable AP in the temperature range of 675–850 °C. Additionally, 89.29% of the phosphorus was enriched in sewage sludge bottom ash and 5.61% was distributed in fly ash, with AP being the primary component in the fly ash at 850 °C. AP content generally increased with decreasing particle size, whereas NAIP content exhibited the opposite tendency, and became stable when the particle size was less than 37.5 μm. Graphical abstract: Highlights: Potential recovery of P was studied by XRD and DSC-TGA by sewage sludge incineration treatment. Phosphorus enriched in SSA and its distribution in fly ash was studied. High temperatures and CaO promote the transformation from NAIP to AP. AP is more stable than NAIP in high temperatures. The reactions between NAIP and CaO at different temperatures were determined.